Molecular clearance of ataxin-3 is regulated by a mammalian E4. - Matsumoto, M.; Yada, M.; Hatakeyama, S.; Ishimoto, H.; Tanimura, T.; Tsuji, S.; Kakizuka, A.; Kitagawa, M.; Nakayama, K.I. (The EMBO Journal, 2004)
Insoluble aggregates of polyglutamine-containing proteins are usually conjugated with ubiquitin in neurons of individuals with polyglutamine diseases. We now show that ataxin-3, in which the abnormal expansion of a polyglutamine tract is responsible for spinocerebellar ataxia type 3 (SCA3), undergoes ubiquitylation and degradation by the proteasome. Mammalian E4B (UFD2a), a ubiquitin chain assembly factor (E4), copurified with the polyubiquitylation activity for ataxin-3. E4B interacted with, and thereby mediated polyubiquitylation of, ataxin-3. Expression of E4B promoted degradation of a pathological form of ataxin-3. In contrast, a dominant-negative mutant of E4B inhibited degradation of this form of ataxin-3, resulting in the formation of intracellular aggregates. In a Drosophila model of SCA3, expression of E4B suppressed the neurodegeneration induced by an ataxin-3 mutant. These observations suggest that E4 is a rate-limiting factor in the degradation of pathological forms of ataxin-3, and that targeted expression of E4B is a potential gene therapy for SCA3.